Effect of ceramic shade on the degree of conversion of a dual-cure resin cement analyzed by FTIR - Passos, Sheila P.; Kimpara, Estevão Tomomitsu [UNESP]; Bottino, Marco A. [UNESP]; Santos, Gildo C.; Rizkalla, Amin S. (Elsevier, 2013)
Objectives: The aim of this research was to evaluate the degree of monomer conversion of different resin cement shades when photocured under different feldspathic ceramic shades. The photocuring time was also evaluated as well as the translucency of each ceramic shade. Methods: Three VITA VM7 ceramic shades (Base Dentin 0M1, Base Dentin 2M2 and Base Dentin 5M3) were used to determine the translucency percentage. A spectrophotometer MiniScan was used to measure the opacity percentage of each specimen (2-mm-thick) and then the translucency was calculated. To measure the degree of conversion (DC), the resin cement (Variolink II; A3 Yellow and transparent) specimens (thickness: 100 μm) were photocured under a ceramic block (2-mm-thick) for 20 or 40 s. Specimens photocured without the ceramic block were used as control. Sixteen groups (n = 3) were evaluated. Micro-ATR/FTIR spectrometry was used to evaluate the extent of polymerization of all specimens after 24 h. The %DC was calculated of experimentally polymerized versus maximally polymerized composite. Results: The translucency percentages of 0M1, 2M2 and 5M3 ceramics were 12.41 (1.02)%, 5.75 (1.91)% and 1.07 (0.03)%, respectively. The %DC of both resin cement shades cured under ceramic 5M3 was significantly lower than the other groups (p < 0.05). The %DC of 0M1 groups exhibited no significant difference from 2M2 groups (p > 0.05), with the exception of the transparent cement photocured for 40 s. Conclusion: Photocuring under 2 mm ceramic showed that the increase in chroma saturation significantly decreased Variolink II resin cement %DC (100-μm-thick). © 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Ceramic shade; Degree of conversion; FTIR; Resin cement shade; A-ceramics; Ceramic blocks; Dual-cure; Feldspathic ceramics; Micro-ATR; Monomer conversions; Photo-curing; Polymerized composites; Resin cement; Significant differences; Cements; Curing; Resins; Ceramic materials